Navigating the contradictions of AI: critiquing AI's standardized English and developing creative bilingual possibilities - Rivero, Edward; Yin, Peng (Frontiers in Education, 2025)
This study examines bilingual pre-service teachers' (PSTs) perceptions and reflections on Artificial Intelligence (AI) technologies in relation to their own biliteracy and pedagogical development. Grounded in a critical language and sociocultural literacy framework, this paper features highlights from a larger research project that examines how PSTs leverage AI to develop academic literacies, create multimodal texts, and design AI-mediated lesson plans in bilingual classrooms. The study participants consist of 13 PSTs from Mandarin (8) and Spanish (5) speaking backgrounds, who were enrolled in a graduate-level teacher preparation course. For this study, we focused on a specific segment of data drawn from a reflective journal activity completed by participants. This reflective journal activity involved (i) reflecting on the affordances and constraints of AI for their own academic literacy development, (ii) designing and evaluating AI-generated multimodal texts for bilingual learners, and (iii) engaging in conversations with AI about bilingual education. Findings reveal that PSTs'engagement with AI in their biliteracy and pedagogical development, is characterized by tensions between its potential to support culturally responsive learning and its constraints undergirded by the ideologies of standardized English and monolingualism. The study concludes by highlighting its pedagogical implications for bilingual teacher education at the tertiary level.